JUDUL ABSTRAK TIDAK TERCANTUM DALAM BAHASA INGGRIS - TIYAN CAHYANINGRUM (NIM : 10213062), DEVI
Zeolites are porous material that can be used ass molecular sieves. Different types of zeolite are based on their porous size and porous shape. Thermal shock is a activation method which is simple and safe because it does not need any hazardous chemicals. This method is used to increase sorption ability of zeolite. Thermal shock is given in low temperature variation which is 250 degree C, 360 degree C and 410 degree C. Result of calculation shows zeolite particle's average diameter is decreasing while thermal shock is adding in all temperature variation. However, it is known that there is a critical radius for zeolite. Thus, zeolite cannot reach lower radius than it's critical radius. Mathematical model is built to explain zeolite's critical radius phenomena which critical radius is inversely to temperature changes.